PENGEMBANGAN MODUL PEMBELAJARAN SENI GRAFIS CETAK DATAR MEDIA KERTAS KARBON PADA MATA PELAJARAN SENI BUDAYA KELAS IX DI SMP NEGERI 22 MAKASSAR - Zubair, Ahmad; Pattaufi, Pattaufi; Yunus, Pangeran Paita (Universitas Negeri Makassar, 2018)
The study aims at developing graphic print art learning module using carbon paper media to grade IX at SMP/MTs in SMPN 22 in Makassar as the site of the research which meet valid criteria to be applied in graphic arts and modification technique learning module using carbon paper media to grade IX at SMP/MTs in SMPN 22 in makassar consisted of teacher’s manual module and student’s manual module and the product obtained would be stated as valid. The model used in this research and development reffered to 4-D Thiagarajan’s model, which consisted of four stages and simplified to two stages, namely defining stages and design stages. The development stage was merely partly. The development of graphic print art learning module using carbon paper media to grade IX at SMP/MTs in SMPN 22 Makassar was validated by one graphic expert and two material experts. The instrument used to collect the data was questionnaire given to the assesors for graphic and material. Data were analyzed by employing descriptive qualitative data analysis. The data result of learning module were counted beforehand quantitatively; then, it was equivalent to qualitative data. The result of the study reveal that in general the graphic print art learning module using carbon paper media to grade IX at SMP/MTs in SMPN 22 in Makassar which was developed had met vilid criteria; this, it is feasible to be continued in trial test to measure the practicality and effectiveness of the learning module.